Analisis Nilai Budaya dalam Legenda di Kabupaten Aceh Tengah - Elvira Nelli; Rajab Bahry; Muhammad Idham (JIM Pendididikan Bahasa dan Sastra Indonesia, 2020)
This study entitled "Analysis Value Culture of Legend In District Aceh Tengah” .The problem in this research is what the value culture in legend of District Aceh Tengah? and How the inward structure in legend of District Aceh Tengah? This study aims to identify the value culture of legend in dictrict Aceh Tengah and to describe of inward srtucture in legend of district Aceh Tengah. This research use descriptive method with approach qualitative. The aggregation of data using techniques listen and help by techniques record. The data source in this reseacrh is community of  District Aceh Tengah who understand of  legend. This legend consists of four title, there are Atang Jungket, Asal Mula Pepayungen, Malim Diwa, and Sengeda and Bener Merie. The results showed that in each legend which research there is value culture related with exploit natural, myth, mutual help, obey with leader, affection, keep of promise, hard work, and cleaver